علاقة طول الحامل بالولادة الباكرة - الأيوب, جهاد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة على 832 حامل في قسم التوليد بمشفى الأسد الجامعي باللاذقية بالفترة ما بين 1/7/2006 و 1/7/2007 وقسمت الحوامل إلى أربع مجموعات المجموعة الأولى وعددها (78) أطوال الحوامل فيها أقصر من 155 سم والمجموعة الثانية وعددها (339) أطوال الحوامل فيها بين 156-160 سم والمجموعة الثالثة وعددها (324) أطوال الحوامل فيها بين 161-170 سم والمجموعة الرابعة وعددها (91) أطوال الحوامل فيها اكبر من 170سم وكان هدف هذه الدراسة تحديد نسبة حدوث الولادة الباكرة في كل مجموعة. إن الولادة الباكرة كانت بنسبة 21.79% في المجموعة الأولى مقابل 14.45% في المجموعة الثانية و 7.40% في المجموعة الثالثة و 3.29% في المجموعة الرابعة. This study was carried out on 832 pregnant women in the Obstetric and Gynecology Department at AL-Assad University Hospital in Lattakia between 1/7/2006 and 1/7/2007. They were divided into four groups: The first group included 78 pregnant women whose heights were ≥ 155cm; the second group consisted of 339 pregnant women whose heights ranged between 156 and 160 cm; the third group comprised 324 pregnant women whose heights ranged between 161 and 170cm; and the fourth group included 91 pregnant women whose heights were < 170cm. The purpose of this study was determine the premature delivery ratios for each group. The ratios of premature delivery in the first group were 21.79% versus 14.45% in the second group, 7.40% in the third group, and 3.29% in the fourth group.